A single training session of visual choice reaction time after mild stroke: A proof of concept - Caires, Tamise Aguiar; Luvizutto, Gustavo José; Dos Santos Vieira, Paula Cíntia; Jablonski, Gabriel; Bazan, Rodrigo [UNESP]; de Oliveira Andrade, Adriano; de Souza, Luciane Aparecida Pascucci Sande (Termedia Sp. z.o.o., 2022)
Purpose. Visual choice reaction time can be measured in reaching, which is an important task to investigate after stroke owing to its high clinical importance in activities of daily living. The study aim was to evaluate the visual choice reaction time during reaching tasks in the ipsilateral and contralateral spaces before and after a single training session of choice reaction time in patients after a mild stroke. Methods. The cross-sectional study involved 7 individuals after a mild stroke. The visual choice reaction time was evaluated during reaching in the affected and unaffected sides in the ipsilateral and contralateral spaces. All individuals trained the choice reaction time during a functional reaching task in a single session. In the training, 6 circles were used in a randomized sequence in 5 blocks, with 10 stimuli per block, for a total of 50 repetitions. Results. There was a significant reduction in the choice reaction time for the unaffected side in the ipsilateral space after training (p = 0.041). The other task conditions did not show a statistical difference, but a clinical relevance based on Cohen’s d (d > 0.60). Conclusions. A single training session can decrease the choice reaction time for the affected side during tasks in the ipsilateral space after a mild stroke.
Keywords: Choice reaction time; Electromyography; Stroke